Influence of standard modifiable risk factors on ventricular tachycardia after myocardial infarction - Deshmukh, Tejas; Kovoor, Joshua G.; Byth, Karen; Chow, Clara K.; Zaman, Sarah; Chong, James J. H.; Figtree, Gemma A.; Thiagalingam, Aravinda; Kovoor, Pramesh (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: Inducible ventricular tachycardia (VT) at electrophysiology study (EPS) predicts sudden cardiac death due to ventricular tachyarrhythmia, the single greatest cause of death within two years after myocardial infarction (MI). OBJECTIVES: We aimed to assess the association between standard modifiable risk factors (SMuRFs) and inducible VT at EPS early after MI. METHODS: Consecutive patients with left ventricle ejection fraction ≤ 40% on day 3-5 after ST elevation myocardial infarction (STEMI) who underwent EPS were recruited prospectively. Positive EPS was defined as induced sustained monomorphic VT cycle length ≥200ms for > 10 seconds, or shorter duration if hemodynamically compromised. The primary outcome was inducibility of VT at EPS and secondary was all-cause mortality on follow up. RESULTS: In 410 eligible patients undergoing EPS soon (median 9 days) after STEMI, 126 had inducible VT. Ex-smokers experienced increased risk of inducible VT (multivariable logistic regression adjusted OR 2.0, p=0.033) compared to current or never smokers who had comparable risk. The presence of any SMuRF apart from current smoker conferred an increased risk of inducible VT (adjusted OR 1.9, p=0.043). Neither the number of SMuRFs nor the presence of any SMuRF were associated with mortality at a median follow up of 5.4 years.In patients with recent STEMI and impaired left ventricular function, the presence of any SMuRF, apart from current smoker, conferred an increased risk of inducible VT at EPS. These results highlight the need to modify SMuRFs in this high risk subset of patients.